2022
DOI: 10.1088/1361-648x/ac4ced
|View full text |Cite
|
Sign up to set email alerts
|

Non-equilibrium thermoelectric transport across normal metal–quantum dot–superconductor hybrid system within the Coulomb blockade regime

Abstract: A detailed investigation of the non-equilibrium steady-state electric and thermoelectric transport properties of a quantum dot coupled to the normal metallic and s-wave superconducting reservoirs (N-QD-S) are provided within the Coulomb blockade regime. Using non-equilibrium Keldysh Green’s function formalism, initially, various model parameter dependence of thermoelectric transport properties are analysed within the linear response regime. It is observed that the single-particle tunnelling close to the superc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…At finite temperature the average superconducting pairing correlation terms i.e. d † iσ d † iσ and d iσ d iσ are negligible and only average occupation n diσ need to be calculated self-consistently [40,43,44]. Thus within the HF mean field approximation the Hamiltonian in equation ( 4) is simplified as…”
Section: Quasi-particlementioning
confidence: 99%
See 1 more Smart Citation
“…At finite temperature the average superconducting pairing correlation terms i.e. d † iσ d † iσ and d iσ d iσ are negligible and only average occupation n diσ need to be calculated self-consistently [40,43,44]. Thus within the HF mean field approximation the Hamiltonian in equation ( 4) is simplified as…”
Section: Quasi-particlementioning
confidence: 99%
“…Recently, very few studies has been conducted on the thermal transport properties of quantum dot-based Josephson junctions i.e when both the leads are superconducting [40,41]. Further, the thermoelectric transport properties of systems where the quantum dot is coupled between normal metal and BCS superconductor (N-QD-S) [42,43,44] and ferromagnet and BCS superconductor (F-QD-S) [45,46,47,48] have been studied recently. Further the thermoelectric transport properties of multi-dot and multi-terminal systems with one superconducting lead are also gaining attention [49,50,51,52,53].…”
Section: Introductionmentioning
confidence: 99%
“…30,[48][49][50][51][52] The few recent studies on two-terminal devices have conrmed that the thermoelectric properties of QD hybrid systems coupled to one conventional lead (metallic or ferromagnetic lead) and one superconducting lead, are remarkably better than those coupled to two conventional leads. 16,28,29,45,47,53 It has been found that the thermoelectric efficiency of the former can even reach several times or even tens of times that of the latter, by comprehensively regulating the superconducting gap, interdot coupling and asymmetric parameters, which can also be additionally enhanced by the interference effect and interdot Coulomb interaction. This is mainly attributed to the unique tunnelling mechanism and high density of states distribution near superconducting gap edges.…”
Section: Introductionmentioning
confidence: 99%
“…The very high density of states near superconducting gap edges changes rapidly with energy, which is mainly responsible for the high thermopower and low thermal conductivity near the superconducting gap edges. However, recent studies have mainly focused on single quantum dot, 16,47 double quantum dot 28,53 and parallel coupled triple quantum dot systems, 29,45 the thermoelectric properties of TTQD coupling to one metallic-metallic and one superconducting lead have not been studied yet.…”
Section: Introductionmentioning
confidence: 99%
“…Recent approaches to this problem exploit tunnel junctions between unequal superconducting electrodes using nonlinearities [4][5][6] or single-electron transistors [7][8][9], hybrid normal-superconductor junctions including quantum dot energy filters [10][11][12][13][14][15], spin-dependent scattering [16][17][18][19][20][21][22][23][24][25][26], photon-assisted tunneling [27], or interference phenomena [28,29]. The gapped density of states has also been successfully used for cooling [30,31] and for power sources [32,33].…”
Section: Introductionmentioning
confidence: 99%